Readiness and efforts of civics teachers in developing literacy and numeracy skills - Winarno, Winarno; Muchtarom, Mohammad; Fauziyah, Husnul (Intelektual Pustaka Media Utama, 2024)
This research aimed to assess the readiness and efforts of civics teachers in developing literacy and numeracy skills. For data collection, qualitative methods including surveys and interviews, were employed. A total of 38 civics teachers from junior high schools in Pacitan Regency, Indonesia were selected based on gender, teaching experience, and certification. The data was analyzed using both qualitative narrative and quantitative descriptive analysis, employing percentages. The results showed that civics teachers demonstrated moderate proficiency in literacy skills, while their numeracy abilities were considered sufficient. In addition, teachers exhibited a greater readiness for literacy-oriented learning compared to numeracy. The efforts made by teachers encompassed four aspects, namely i) collaborating with colleagues and implementing student-centered collaborative learning, ii) developing a culture of literacy and numeracy through training and discussions, iii) seeking out learning resources and media that supported literacy and numeracy, and iv) promoting reading, annotating texts, and analyzing numeracy-related readings.